2014
DOI: 10.1155/2014/562625
|View full text |Cite
|
Sign up to set email alerts
|

Generating and Reversing Chronic Wounds in Diabetic Mice by Manipulating Wound Redox Parameters

Abstract: By 2025, more than 500 M people worldwide will suffer from diabetes; 125 M will develop foot ulcer(s) and 20 M will undergo an amputation, creating a major health problem. Understanding how these wounds become chronic will provide insights to reverse chronicity. We hypothesized that oxidative stress (OS) in wounds is a critical component for generation of chronicity. We used the db/db mouse model of impaired healing and inhibited, at time of injury, two major antioxidant enzymes, catalase and glutathione perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(143 citation statements)
references
References 63 publications
4
136
0
Order By: Relevance
“…35 Furthermore, collagen-induced platelet activation in wounds can produce high amounts of H 2 O 2 that could stimulate platelet aggregation pathways. 36 We recently showed that TNFSF14/LIGHT -/-mice have high levels of oxidative stress early in wound healing with increased presence of H 2 O 2 and isoprostanes, 18 suggesting the enhancement of the platelet activation we now report here. Moreover, reactive oxygen species frequently observed in impaired and chronic wounds have increasingly been shown to be major players in the activation of platelets and to cause thrombus formation.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…35 Furthermore, collagen-induced platelet activation in wounds can produce high amounts of H 2 O 2 that could stimulate platelet aggregation pathways. 36 We recently showed that TNFSF14/LIGHT -/-mice have high levels of oxidative stress early in wound healing with increased presence of H 2 O 2 and isoprostanes, 18 suggesting the enhancement of the platelet activation we now report here. Moreover, reactive oxygen species frequently observed in impaired and chronic wounds have increasingly been shown to be major players in the activation of platelets and to cause thrombus formation.…”
Section: Discussionsupporting
confidence: 54%
“…The procedure used was performed as previously described. 18 Briefly, mice were anesthetized with a single intraperitoneal injection of ketamine (80 mg/kg body weight)/xylazine (16 mg/kg body weight). Fullthickness 7 mm punch wounds (excision of the skin and the underlying panniculus carnosus) were made on the back of the mice 24 h after nairing and shaving the hair.…”
Section: Methodsmentioning
confidence: 99%
“…17 It has been suggested in an animal model that application of strong antioxidants reduces ROS to normal levels, which results in the reverse of the chronicity of wounds and improves healing. 18 Furthermore, chronic wounds are characterized by senescent cell populations with impaired proliferative and secretory capacities, rendering them unresponsive to typical wound healing signals. 15 It has been reported that fibroblasts from venous and PUs are senescent and have a diminished ability to proliferate.…”
Section: Physiology Of Wound Healingmentioning
confidence: 99%
“…In one chronic mouse model, db/db mice (diabetic mice that have a spontaneous mutation in the leptin receptor, resulting in insulin tolerance) were given a full thickness excision wound, and over time were infected with bacterial species considered to be part of the mouse native skin flora: S. aureus, coagulase-negative Staphylococcus sp., Enterococcus sp., Enterobacter cloacae and Pseudomonas sp. [115]. The microbes developed biofilms on the wound and notably impaired wound healing compared with the noninfected mice, thus creating a chronic infection [116].…”
Section: Skin and Soft Tissue Infectionsmentioning
confidence: 99%